Edmund Physick family papers - Physick, Edmund, 1725 or 1726-1804.
Chiefly account books and receipt books along with correspondence, notes, and other papers of the Physick and Syng families of Philadelphia, Pa. Documents the settlement of the estates of family members as well as household, business, and farming affairs including Philadelphia real estate transactions. Family members represented include Edmund Physick; his wife, Abigail Syng Physick; her father, Philip Syng; their son, Philip Syng Physick, and daughter, Abigail Physick; and Theodore Physick. Includes two volumes pertaining to Edmund Physick's work as agent for John Penn (1729-1795) and John Penn (1760-1834). Documents the construction of the Penn family mansion, Lansdowne, on the Schuylkill River, Pa. Also includes four volumes documenting the estates of brothers James and Robert Bremner; a receipt book belonging to Parry Hall; an order-book (1821-1822) of the USS Dolphin (Schooner) kept by David Conner; and a fragment of an 1829 logbook of the USS Erie (Sloop of war).
Microfilm edition available
Physick and Syng family members including Edmund Physick, Pennsylvania official and Penn family agent; his wife, Abigail Syng Physick; her father, Philadelphia silversmith Philip Syng; their son, surgeon Philip Syng Physick; their daughter, Abigail Physick, who managed real estate in Philadelphia; and physician Theodore Physick.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bremner, James, -- -approximately 1783 -- Estate; Bremner, Robert, -- -approximately 1790 -- Estate; Conner, David, -- 1792-1856.; Hall, Parry, -- 1755?-1793.; Penn, John, -- 1729-1795.; Penn, John, -- 1760-1834.; Physick, Abigail, -- 1763-1854.; Physick, Abigail Syng, -- -1791.; Physick, Philip Syng, -- 1768-1837.; Physick, Theodore, -- 1805-1834.; Syng, Philip, -- 1703-1789.; Penn family; Penn family -- Homes and haunts -- Pennsylvania; Physick family; Syng family; Dolphin (Schooner : 1821-1835); Erie (Sloop of war); Agriculture -- Pennsylvania; Ship's papers -- 19th century; Pennsylvania -- History; Pennsylvania -- Social life and customs; Philadelphia (Pa.) -- Commerce; Philadelphia (Pa.) -- Social life and customs; Public officials -- Pennsylvania